Polyoxometalate-derived electrode materials, methods of making and using the same

CN122957880APending Publication Date: 2026-10-23HUANGHUAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611067464.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]为了克服上述现有技术的缺点,本发明的目的在于提供多金属氧酸盐衍生的电极材料及其制备方法和应用,用以解决多金属氧酸盐衍生电极材料制备过程中存在二次团聚的技术问题

Benefits of technology

本发明提供的多金属氧酸盐衍生的电极材料的制备方法,1)没有直接选取亚纳米尺寸的多金属氧酸盐作为构筑单元与有机配合物复合,而是采用草酸调节单体金属氧酸盐反应溶液的pH,在三聚氰胺的限域环境下,逐步原位生长成单分散的多金属氧酸盐前驱体;通过构建特殊的纳米限域环境,实现了多金属氧酸盐与有机配体之间的精准嵌入或单分子层级相互作用;2)合成电极材料的金属盐、三聚氰胺及草酸原料来源广泛,且成本低廉,安全性高,合成过程绿色可持续,具有较高的经济效益;3)通过一步水热法即可实现多金属氧酸盐原位生长及与三聚氰胺的组装,合成过程简单高效,通过增大反应的投料量,可以一锅合成以千克为单位的粉末,有利于工业规模生产与应用;4)得到的多金属氧酸盐前驱体分子内部存在强烈的化学作用力,通过简单热硫化,能够促使有机物限域多金属氧酸盐衍生为高活性碳层包覆的金属硫化物。因此,通过将多金属氧酸盐转化成金属硫化物,有机配体转化成碳层,将碳层包裹在金属硫化物的表面,制备多金属氧酸盐衍生的电极材料,制备流程简单,可重复性强,不仅保持了多金属氧酸盐的高分散性,还原位转化成高活性的金属硫化物,形成结构稳定、导电性较好的多金属氧酸盐衍生的电极材料,能够克服现有多金属氧酸盐衍生电极材料制备与微观结构调控技术存在的二次团聚局限,使制备的多金属氧酸盐衍生的电极材料具有较好的导电性和高活性反应位点,界面结构稳定持久,比表面积大,分散性高。基于得到的多金属氧酸盐衍生的电极材料优越的微纳构型制备钠离子电池,不仅提升了电池电极材料的离子、电子传输特性,还可有效抑制金属硫化物充放电过程中界面失活、结构坍塌等问题,使制得的电池体现出了可逆容量高、倍率性能优异和循环寿命超长等优势,在钠离子电池储能领域具有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122957880A_ABST
    Figure CN122957880A_ABST
Patent Text Reader

Abstract

The application discloses a polyoxometalate-derived electrode material and a preparation method and application thereof, and belongs to the technical field of material science and battery materials. A melamine dispersion liquid is mixed with an oxalic acid solution to obtain a solution B; a metal salt solution is added to the solution B to react, a solution C is obtained, and a hydrothermal reaction is performed to obtain a polyoxometalate precursor; and a hot vulcanization treatment is performed to obtain the polyoxometalate-derived electrode material. The electrode prepared based on the material exhibits high specific capacity, excellent cycle stability and rate performance as a negative electrode of a sodium ion battery, and the material synthesis steps are simple, the material has strong repeatability, and the material has good economic benefits and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of materials science and battery materials technology, specifically relating to polyoxometalate-derived electrode materials, their preparation methods, and applications. Background Technology

[0002] Polyoxometalates possess strong redox activity and multi-electron transfer properties, making them highly promising electrode materials. However, their easy solubility, agglomeration, and poor conductivity hinder their application in energy storage. To address these issues, researchers have utilized organic ligands (such as those containing -COOH or -NH2 functional groups) to form precursors with polyoxometalates through coordination or hydrogen bonding, followed by strategies such as pyrolysis and reconstruction to prepare high-performance electrode materials. This strategy not only inhibits the leaching of polyoxometalates in polar solvents but also prevents their agglomeration, improving the material's activity and stability. Although the precursor structures formed by polyoxometalates and organic compounds are relatively stable at low temperatures (<200℃), key challenges remain in subsequent thermal polycondensation or pyrolysis and reconstruction processes due to the significant difference between the sub-nanometer size (typically <1 nm) of polyoxometalates and the size of organic ligands or polymeric frameworks. This mismatch prevents the organic ligands from effectively confining the movement of polyoxometalates during heat treatment. Driven by heat, the van der Waals forces or electrostatic interactions between polyoxometalates are enhanced, making them prone to secondary aggregation. This not only leads to a significant loss of active sites but also significantly reduces the specific surface area of ​​the material.

[0003] Currently, modification methods for polyoxometalate-derived electrode materials mostly focus on macroscopic loading or compositing, lacking precise control at the microscopic level. Therefore, there is an urgent need to develop a novel strategy to overcome the secondary agglomeration problem during the preparation of polyoxometalate-derived electrode materials, thereby improving the rate performance and cycle performance of the electrode materials. Summary of the Invention

[0004] In order to overcome the shortcomings of the prior art, the present invention aims to provide a polyoxometalate-derived electrode material, its preparation method and application, so as to solve the technical problem of secondary agglomeration in the preparation process of polyoxometalate-derived electrode materials.

[0005] To achieve the above objectives, the present invention employs the following technical solution: The first aspect of the present invention discloses a method for preparing a polyoxometalate-derived electrode material, wherein a melamine dispersion is mixed with an oxalic acid solution to obtain a solution B; a metal salt solution is added to solution B, and the mixture reacts to obtain a solution C; a hydrothermal reaction is performed to obtain a polyoxometalate precursor; and a thermal sulfidation treatment is performed to obtain the polyoxometalate-derived electrode material.

[0006] Preferably, the melamine dispersion is obtained by dispersing melamine in deionized water.

[0007] Preferably, the concentration of the melamine dispersion is 0.08 mol / L.

[0008] Preferably, the concentration of the oxalic acid solution is 0.2 mol / L, and the molar ratio of melamine to oxalic acid is 1:(0.25~1).

[0009] Preferably, the metal salt is one of sodium molybdate, sodium tungstate, and sodium vanadate.

[0010] Preferably, the amount of the metal salt is 1.2 mmol.

[0011] Preferably, the thermal vulcanization step is as follows: the polyoxometalate precursor and sulfur powder are mixed at a mass ratio of 1:2 and calcined in an argon atmosphere.

[0012] More preferably, the calcination temperature is carried out in a programmed heating mode, with a heating rate of 1℃ / min to 200℃, held for 2 h, and then a heating rate of 1.5℃ / min to 570℃, held for 2~3 h.

[0013] In a second aspect, the present invention discloses a polyoxometalate-derived electrode material prepared by the above-described preparation method.

[0014] A third aspect of the present invention discloses the application of polyoxometalate-derived electrode materials in the preparation of sodium-ion batteries.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The method for preparing polyoxometalate-derived electrode materials provided by this invention: 1) Instead of directly selecting sub-nanometer-sized polyoxometalates as building blocks to combine with organic complexes, oxalic acid is used to adjust the pH of the monomeric polyoxometalate reaction solution, and monodisperse polyoxometalate precursors are gradually grown in situ under the confinement environment of melamine; by constructing a special nano-confined environment, precise intercalation or monomolecular-level interaction between polyoxometalates and organic ligands is achieved; 2) The metal salts, melamine, and oxalic acid raw materials for synthesizing the electrode materials are widely available, low in cost, and highly safe. The synthesis process is green and sustainable, with high economic benefits; 3) The in-situ growth of polyoxometalates and their assembly with melamine can be achieved through a one-step hydrothermal method. The synthesis process is simple and efficient. By increasing the amount of reactants, powders in kilograms can be synthesized in one batch, which is beneficial for industrial-scale production and application; 4) The obtained polyoxometalate precursor molecules have strong chemical forces within them. Through simple thermal sulfidation, organic confinement of polyoxometalates can be promoted to degenerate into highly active carbon-coated metal sulfides. Therefore, by converting polyoxometalates into metal sulfides, organic ligands into carbon layers, and then coating the surface of the metal sulfides with these carbon layers, polyoxometalate-derived electrode materials can be prepared. This process is simple, highly reproducible, and maintains the high dispersibility of polyoxometalates. The reduction sites are converted into highly active metal sulfides, forming structurally stable and highly conductive polyoxometalate-derived electrode materials. This overcomes the limitations of secondary agglomeration in existing polyoxometalate-derived electrode material preparation and microstructure control techniques. The prepared polyoxometalate-derived electrode materials exhibit good conductivity and highly active reaction sites, with a stable and durable interface structure, large specific surface area, and high dispersibility. Sodium-ion batteries based on the superior micro / nano configuration of these polyoxometalate-derived electrode materials not only improve the ion and electron transport characteristics of the battery electrode materials but also effectively suppress interfacial deactivation and structural collapse during metal sulfide charging and discharging. The resulting batteries exhibit advantages such as high reversible capacity, excellent rate performance, and ultra-long cycle life, showing broad application prospects in the field of sodium-ion battery energy storage.

[0016] Furthermore, this method has universality and application value for the in-situ growth of different types of polyoxometalates (including molybdenum polyacidates, tungsten polyacidates, and vanadium polyacidates).

[0017] The present invention also provides an electrode material derived from polyoxometalates obtained by the above method, which has a large specific surface area and a tight interfacial interaction, which not only facilitates electrolyte wetting and ion transport, but also effectively alleviates the problem of metal sulfide structure collapse during charging and discharging. Attached Figure Description

[0018] Figure 1The images shown are XRD and SEM images of the heptamolybdate precursor obtained in Example 1; where a is the XRD image and b is the SEM image. Figure 2 The images shown are XRD and SEM images of carbon-coated MoS2 derived from heptamolybdate obtained in Example 1; where a is the XRD image and b is the SEM image. Figure 3 The graphs show the cycle performance and rate performance of carbon-coated MoS2 derived from heptamolybdate obtained in Example 1 as a sodium-ion battery anode; where a is the cycle performance graph and b is the rate performance graph. Figure 4 The images shown are XRD and SEM images of the dodecantungstate precursor obtained in Example 2; where a is the XRD image and b is the SEM image. Figure 5 The images show the XRD and SEM images of carbon-coated WS2 derived from dodecantungstate obtained in Example 2; where a is the XRD image and b is the SEM image. Figure 6 The graphs show the cycle performance and rate performance of WS2, which is carbon-coated with dodecantungstate derived from Example 2, as a sodium-ion battery anode; where a is the cycle performance graph and b is the rate performance graph. Figure 7 The images shown are XRD and SEM images of the decavanadate precursor obtained in Example 3; where a is the XRD image and b is the SEM image. Figure 8 The images shown are XRD and SEM images of the decavanadate-derived electrode material obtained in Example 3; where a is the XRD image and b is the SEM image. Figure 9 The graphs show the cycle performance and rate performance of the decavanadate-derived electrode material obtained in Example 3 as the negative electrode of a sodium-ion battery; where a is the cycle performance graph and b is the rate performance graph. Detailed Implementation

[0019] To enable those skilled in the art to understand the features and effects of the present invention, the following descriptions and definitions are only general descriptions of the terms and expressions mentioned in the specification. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in the event of any conflict, the definitions in this specification shall prevail.

[0020] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0021] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0022] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0023] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0024] This invention provides a method for preparing polyoxometalate-derived electrode materials, comprising the following steps: S1. Melamine is dispersed in deionized water at 80℃ until it is completely dissolved to obtain solution A; then oxalic acid solution is added to solution A to obtain solution B. The concentration of solution A is 0.08 mol / L, the concentration of oxalic acid solution is 0.2 mol / L, and the molar ratio of melamine to oxalic acid is 1:(0.25~1). S2. Add the metal salt solution dropwise to solution B obtained in S1, stir and react for 20-30 min to obtain solution C; transfer solution C to a reaction vessel and carry out a hydrothermal reaction at 130℃. After 10 h, stop the reaction and wash and dry the precipitate to obtain the polyoxometalate precursor. The metal salt is, but is not limited to, one of sodium molybdate, sodium tungstate, and sodium vanadate; the amount of the metal salt is 1.2 mmol. S3. Mix the polyoxometalate precursor with sulfur powder at a mass ratio of 1:2, and then calcine in an argon atmosphere to obtain the polyoxometalate-derived electrode material. The roasting temperature is carried out in a tube furnace using a programmed heating mode, with a heating rate of 1℃ / min to 200℃, held for 2 h, and then a heating rate of 1.5℃ / min to 570℃, held for 2~3 h.

[0025] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading this description, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined in this application.

[0026] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under standard conditions or as recommended by the manufacturer. In the following examples, melamine was purchased from Innochem (A23204); oxalic acid was purchased from Innochem (A18284); sodium molybdate was purchased from Macklin (S824536); sodium tungstate was purchased from Macklin (S859551); sodium orthovanadate was purchased from Innochem (A30029); ethanol was purchased from Innochem (A20072); sulfur powder was purchased from Aladdin (S105118); conductive carbon black was purchased from Innochem (A00324); polyvinylidene fluoride was purchased from Innochem (A68262); and so on. N -Methylpyrrolidone was purchased from Innochem, catalog number A28738; the electrolyte used (1 mol / L sodium hexafluorophosphate dispersed in diethylene glycol dimethyl ether) was purchased from Duoduo Chemical, catalog number NP-005; all other raw materials used, unless otherwise specified, were conventional commercial products with specifications in the art.

[0027] Example 1 1. Preparation method of polyoxometalate-derived electrode materials (1) Weigh 0.5 g (4 mmol) of melamine and disperse it in 50 mL of deionized water. Stir and dissolve at 80 °C to obtain solution A. Then add 20 mL of 0.2 mol / L oxalic acid solution to solution A to obtain solution B.

[0028] (2) 1.2 mmol sodium molybdate solution (dissolved in 5 mL of deionized water) was added dropwise to solution B, and the mixture was stirred for 20 min to obtain reaction solution C. Solution C was transferred to a reaction vessel and reacted in an oven at 130℃ for 10 h to obtain a white precipitate. The white precipitate was then filtered and washed three times with ethanol and water, and dried in a vacuum oven at 60℃ for 12 h to obtain a white heptamolybdate precursor ( Figure 1XRD patterns confirmed the in-situ synthesis of the heptamolybdate precursor, which was composed of melamine / cyanuric acid and heptamolybdate. SEM images showed that the obtained heptamolybdate precursor had a uniform lamellar structure.

[0029] (3) Take 0.15 g of heptamolybdate precursor and mix it with 0.3 g of sulfur powder. Place it under an argon atmosphere, first raise the temperature to 200℃ at 1℃ / min and hold for 2 h, then raise the temperature to 570℃ at 1.5℃ / min and hold for 3 h to obtain carbon-coated MoS2 derived from heptamolybdate. Figure 2 XRD patterns show that the thermally vulcanized heptamolybdate is converted into MoS2, forming carbon-coated MoS2; SEM images show that the thermally vulcanized material still retains a lamellar structure.

[0030] 2. Performance testing of polyoxometalate-derived electrode materials The carbon-coated MoS2 prepared in step 1 was mixed evenly with conductive carbon black and polyvinylidene fluoride at a mass ratio of 7:2:1, and then added... N Using methylpyrrolidone as a solvent, it was coated onto pure copper foil and vacuum dried at 80°C for 12 h. Pure sodium sheet was used as the counter electrode, glass fiber was used as the separator, and 1 mol / L sodium hexafluorophosphate was dispersed in diethylene glycol dimethyl ether as the electrolyte. Electrochemical tests were then performed using a button half-cell at voltages of 0.01–3 V.

[0031] Sodium-ion battery cycle performance such as Figure 3 As shown in Figure a, it can be seen that after 1000 cycles at a high current density of 2 A / g, the obtained battery still maintains a capacity of 467.1 mAh / g, indicating that this novel electrode has excellent structural stability; the rate performance of the sodium-ion battery is as follows... Figure 3 As shown in Figure b, the capacity can be achieved at a current density of 0.1 A / g, reaching 734.0 mAh / g. When the current density is increased to 1 A / g, the capacity reaches 647.1 mAh / g, and when the current density is further increased to 50 A / g, the capacity reaches 224.9 mAh / g. After switching the current density back to 0.1 A / g at the 66th cycle, the capacity can still be maintained at 751.2 mAh / g, demonstrating the excellent rate performance of the electrode material.

[0032] Example 2 1. Preparation method of polyoxometalate-derived electrode materials (1) Weigh 0.5 g (4 mmol) of melamine and disperse it in 50 mL of deionized water. Stir and dissolve at 80 °C to obtain solution A. Then add 5 mL of 0.2 mol / L oxalic acid solution to solution A to obtain solution B.

[0033] (2) 1.2 mmol sodium tungstate solution (dissolved in 5 mL of deionized water) was added dropwise to solution B, and the mixture was stirred for 25 min to obtain reaction solution C. Solution C was transferred to a reaction vessel and reacted in an oven at 130℃ for 10 h to obtain a white precipitate. The white precipitate was then filtered and washed three times with ethanol and water, and dried in a vacuum oven at 60℃ for 12 h to obtain a white dodecyltungstate precursor ( Figure 4 XRD patterns confirmed the in-situ synthesis of the dodecyltungstate precursor, which was composed of melamine / cyanuric acid and dodecyltungstate. SEM images showed that the obtained dodecyltungstate precursor had a uniform planar structure.

[0034] (3) Take 0.15 g of dodecantungstate precursor and 0.3 g of sulfur powder, mix them, place them in an argon atmosphere, first heat to 200℃ at 1℃ / min, hold for 2 h, then heat to 570℃ at 1.5℃ / min, hold for 2 h, to obtain carbon-coated WS2 derived from dodecantungstate ( Figure 5 XRD patterns show that dodecantungstate is thermally sulfided into WS2, forming a carbon-coated WS2 electrode material; SEM images show that the thermally sulfided material has a uniform thin-layer sheet structure.

[0035] 2. Performance testing of polyoxometalate-derived electrode materials The carbon-coated WS2 prepared in step 1 was mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 7:2:1. N-methylpyrrolidone was added as a solvent, and then the mixture was coated onto pure copper foil and vacuum dried at 80°C for 12 h. Pure sodium sheet was used as the counter electrode, glass fiber was used as the separator, and 1 mol / L sodium hexafluorophosphate was dispersed in diethylene glycol dimethyl ether as the electrolyte. Electrochemical tests were then performed using a button half-cell at a voltage of 0.01~3 V.

[0036] Sodium-ion battery cycle performance such as Figure 6 As shown in Figure a, it can be seen that after 1000 cycles at a high current density of 2 A / g, the obtained battery still maintains a capacity of 336.1 mAh / g, indicating that this novel electrode has excellent structural stability; the rate performance of the sodium-ion battery is as follows... Figure 6 As shown in Figure b, the capacity can be achieved at a current density of 0.1 A / g, reaching 586.0 mAh / g. When the current density is increased to 1 A / g, the capacity reaches 502.5 mAh / g, and when the current density is further increased to 50 A / g, the capacity reaches 257.2 mAh / g. After switching the current density back to 0.1 A / g at the 66th cycle, the capacity can still be maintained at 633.6 mAh / g, demonstrating the excellent rate performance of the electrode material.

[0037] Example 3 1. Preparation method of polyoxometalate-derived electrode materials (1) Weigh 0.5 g (4 mmol) of melamine and disperse it in 50 mL of deionized water. Stir and dissolve at 80 °C to obtain solution A. Then add 10 mL of 0.2 mol / L oxalic acid solution to solution A to obtain solution B.

[0038] (2) 1.2 mmol sodium orthovanadate solution (dissolved in 5 mL of deionized water) was added dropwise to solution B, and the mixture was stirred for 30 min to obtain reaction solution C. Solution C was transferred to a reaction vessel and reacted in an oven at 130℃ for 10 h to obtain a dark green precipitate. The dark green precipitate was then filtered and washed three times with ethanol and water, and dried in a vacuum oven at 60℃ for 12 h to obtain a dark green decavanadate precursor. Figure 7 XRD patterns confirmed the in-situ synthesis of the decavanadate precursor, which was composed of melamine / cyanuric acid and decavanadate. SEM images showed that the obtained decavanadate precursor had a uniform columnar structure.

[0039] (3) Take 0.15 g of decavanadate precursor and mix it with 0.3 g of sulfur powder. Place it under an argon atmosphere, first raise the temperature to 200℃ at 1℃ / min and hold for 2 h, then raise the temperature to 570℃ at 1.5℃ / min and hold for 2.5 h to obtain the electrode material derived from decavanadate. Figure 8 XRD patterns confirmed the thermal sulfidation of decavanadate into V. 5.4 S8, forming carbon-coated V 5.4 S8 electrode material; SEM images show that the obtained decavanadate-derived electrode material is a columnar structure assembled from thin sheet layers.

[0040] 2. Performance testing of polyoxometalate-derived electrode materials The prepared decavanadate-derived electrode material was mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 7:2:1. N-methylpyrrolidone was added as a solvent, and then the mixture was coated onto pure copper foil and vacuum dried at 80°C for 12 hours. Pure sodium sheet was used as the counter electrode, glass fiber was used as the separator, and 1 mol / L sodium hexafluorophosphate was dispersed in diethylene glycol dimethyl ether as the electrolyte. Electrochemical tests were then performed using a button half-cell at a voltage of 0.01~3 V.

[0041] Sodium-ion battery cycle performance such as Figure 9As shown in Figure a, it can be seen that after 1000 cycles at a high current density of 2 A / g, the obtained battery still maintains a capacity of 421.0 mAh / g, indicating that this novel electrode has excellent structural stability; the rate performance of the sodium-ion battery is as follows... Figure 9 As shown in Figure b, the capacity can be achieved at a current density of 0.1 A / g, reaching 763.2 mAh / g. When the current density is increased to 1 A / g, the capacity reaches 715.4 mAh / g, and when the current density is further increased to 50 A / g, the capacity reaches 407.2 mAh / g. After switching the current density back to 0.1 A / g at the 66th cycle, the capacity can still be maintained at 788.6 mAh / g, demonstrating the excellent rate performance of the electrode material.

[0042] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.

Claims

1. A method for preparing electrode materials derived from polyoxometalates, characterized in that, Melamine dispersion was mixed with oxalic acid solution to obtain solution B; metal salt solution was added to solution B and reacted to obtain solution C. Hydrothermal reaction was carried out to obtain polyoxometalate precursor; thermal sulfidation treatment was performed to obtain polyoxometalate-derived electrode material.

2. The method for preparing the polyoxometalate-derived electrode material according to claim 1, characterized in that, The melamine dispersion was obtained by dispersing melamine in deionized water.

3. The method for preparing the polyoxometalate-derived electrode material according to claim 1, characterized in that, The concentration of the melamine dispersion was 0.08 mol / L.

4. The method for preparing the polyoxometalate-derived electrode material according to claim 1, characterized in that, The concentration of the oxalic acid solution is 0.2 mol / L, and the molar ratio of melamine to oxalic acid is 1:(0.25~1).

5. The method for preparing the polyoxometalate-derived electrode material according to claim 1, characterized in that, The metal salt is one of sodium molybdate, sodium tungstate, and sodium vanadate.

6. The method for preparing the polyoxometalate-derived electrode material according to claim 1, characterized in that, The amount of the metal salt is 1.2 mmol.

7. The method for preparing the polyoxometalate-derived electrode material according to claim 1, characterized in that, The thermal vulcanization process involves mixing the polyoxometalate precursor with sulfur powder at a mass ratio of 1:2 and calcining it in an argon atmosphere.

8. The method for preparing the polyoxometalate-derived electrode material according to claim 7, characterized in that, The calcination temperature is controlled by a programmed temperature increase mode, with a heating rate of 1℃ / min to 200℃, held for 2 h, and then heated to 570℃ at a rate of 1.5℃ / min, held for 2~3 h.

9. Electrode materials derived from polyoxometalates prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the polyoxometalate-derived electrode material according to claim 9 in the preparation of sodium-ion batteries.